The Wordwall Supported Mathematics Achievement in Elementary School Classrooms: Wordwall Mendukung Peningkatan Prestasi Matematika di Kelas Sekolah Dasar - Endah Ummu Habibah; Moch. Bahak Udin By Arifin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background The integration of digital learning media has become increasingly important in elementary mathematics instruction to create engaging and student-centered learning environments. Specific Background Many classrooms still rely on conventional methods that limit students’ participation and contribute to low learning outcomes in geometry topics. Knowledge Gap Although interactive platforms such as Wordwall are widely available, empirical evidence regarding their classroom application in primary mathematics remains limited. Aims This study aimed to examine the use of the Wordwall application in supporting students’ mathematics learning outcomes on plane geometry materials. Results Classroom implementation showed higher post-learning scores, improved participation, and more active student responses compared with previous conventional instruction. Novelty The study provides contextual evidence of integrating a game-based digital platform directly into daily classroom practice at the elementary level. Implications The findings suggest that structured use of interactive digital media can support more engaging mathematics lessons and contribute to better learner achievement and classroom interaction. Keywords : Wordwall, Elementary Mathematics, Digital Learning Media, Learning Outcomes, Interactive Instruction Key Findings Highlights: Post-test scores exceeded initial performance levels Learners showed stronger classroom participation Game-based tasks supported concept understanding